Cultural Influences and Interactions in the ESL Classroom - Otherine J. Neisler; Alyssa Nota (Educational Considerations, 1999)
There are many students like Esperanza in American schools today. Cisneros’ character finds her identity anchored in her Hispanic name, yet is aware of the cultural diversity around her, particularly in school. Regardless of ethnic or linguistic background, students are influenced on a daily basis by cultural factors.